1989
DOI: 10.1002/jlb.45.6.529
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Regulation of FMLP Receptors on Human Neutrophils

Abstract: Polymorphonuclear leukocytes (PMNs) from subjects diagnosed as having juvenile periodontitis (JP) have been categorized on the basis of their chemotactic (CTX) response to f-met-leu-phe (FMLP) when assayed concurrently with PMNs from periodontally healthy subjects (HP). When PMNs from JP groups demonstrating depressed CTX were assayed for lysosomal enzyme secretion (LES) in response to FMLP, there were no significant differences with respect to rate or amount. Significant differences were observed between HP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Chemotaxis dysfunction in humans with juvenile periodontitis is also accompanied by diminished receptor-mediated binding of chemoattractant. The neutrophils exhibit fewer than normal cell surface receptors for fMLP [38].…”
Section: Discussionmentioning
confidence: 94%
“…Chemotaxis dysfunction in humans with juvenile periodontitis is also accompanied by diminished receptor-mediated binding of chemoattractant. The neutrophils exhibit fewer than normal cell surface receptors for fMLP [38].…”
Section: Discussionmentioning
confidence: 94%
“…Bacterial invasion in the gingival crevice initiates the elaboration of a variety of substances which have the ability to attract PMN to the site of inflammation (chemotaxis). Chemotaxis disorders of peripheral blood PMN have been described in some forms of early onset periodontitis (EOP) including localised early onset periodontitis (LEOP), generalised early onset periodontitis (GEOP), and pre-pubertal periodontitis (Page & Schroeder 1982, Van Dyke et al 1981, Van Dyke et al 1985, 1987, Coles et al 1989, Daniel et al 1993. Deficiencies of neutrophil function often result in increased susceptibility to periodontitis.…”
mentioning
confidence: 99%
“…Deficiencies of neutrophil function often result in increased susceptibility to periodontitis. Chemotaxis disorders of peripheral blood PMN have been described in some forms of early onset periodontitis (EOP) including localised early onset periodontitis (LEOP), generalised early onset periodontitis (GEOP), and pre-pubertal periodontitis (Page & Schroeder 1982, Van Dyke et al 1981, Van Dyke et al 1985, 1987, Coles et al 1989, Daniel et al 1993). These authors reported mainly about a reduced chemotactic function in LEOP patients, but others have discussed an enhanced chemotactic response of peripheral blood PMN in these periodontitis forms (Kinane et al 1989, Repo et al 1990).…”
mentioning
confidence: 99%